Intellectual property contribution with regard to rice genetic resources by tribes of South Oriáa, India - Tripathy, S.=700 1 Gurung, P.; Das Sharma, S.
(En, Fr, Es)
ilus., 2 ref.
Keywords: ORYZA SATIVA; VARIACION GENETICA; RECURSOS GENETICOS; INDIA